TAX ACCOUNTING: THE EFFECTS OF SOCIAL SECURITY CONTRIBUTIONS OF RATES ON INTERMUNICIPAL PASSENGER TRANSPORT IN RIO GRANDE DO SUL - Barth, Victor Scur; Souza, Angela Rozane Leal de; de Oliveira, Letíca (Contextus - Revista Contemporânea de Economia e Gestão, 2016)
From 2011 on, when the “Plano Brasil Maior" was launched, Brazil has adopted measures, among them the creation of social security contributions on gross revenues, replacing INSS employer on the payroll, including the public transport in this exoneration from 2013 on. The objective was to analyze the influence of tax exemption in the calculation of intercity transportation fares, evaluating issues relating to the economic balance of public service providers, in the years 2013 and 2014. Data were collected from reports available on the website of AGERGS, prepared for such years. The main results of the survey indicate that there was a reduction in the value of tariff coefficient of all transport systems regulated by the agency, highlighting the southern urban agglomeration system. It was found in this study that the impacts of exoneration in the tariff coefficients are around 2.5% to 4.5%. This change affected the structure of the companies, influencing the accounting breakeven and asset turnover.